Stereoretentive trifluoromethylthiolation of (E)‑styrylboronic acid with AgSCF3 or N-trifluoromethylthiosuccinimide. (3rd August 2022) - Zheng, Changge; Ma, Mingyu; Huang, Shuai; Jiang, Chao; Liu, Yang; Fu, Yingying; Zhao, Kui; Feng, Ruilong; Hong, Jianquan
Graphical abstract: A stereoretentive trifluoromethylthiolation of styreneboronic with AgSCF3 or N -trifluoromethylthiosuccinimide has been developed under mild reaction conditions stereospecific product. Highlights: Stereoretentive trifluoromethylthiolation for of (E) -styrylboronic acid. Using non-toxic, inexpensive, stable and easy-to-handle trifluoromethylthiolated reagent. Functional group tolerance, high yield and excellent stereoselectivity. Stereospecific product of direct trifluoromethylthiolation vinyl under mild reaction conditions. Abstract: A stereoretentive trifluoromethylthiolation of styrylboronic acids with AgSCF3 or N -trifluoromethylthiosuccinimide has been developed under mild reaction conditions. This synthetic method for vinyl trifluoromethyl thioethers possesses good functional group tolerance, high yield and excellent stereoselectivity with AgSCF3 as the SCF3 source. The stereospecificity of the reaction could been achieved through the trifluoromethylthiolation of β ‑styrylboronic acids with N -trifluoromethylthiosuccinimide.